2009
DOI: 10.1002/cncr.24334
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and treatment modalities for African American women diagnosed with stage III breast cancer

Abstract: BACKGROUND: Stage III breast cancers account for about 6% to 7% of all invasive breast cancers diagnosed annually in the United States. In African American (AA) women, the incidence of stage III breast cancers is almost double that in Caucasian women. The aim of this study was to correlate age, receptor status, nuclear grade, and differences in treatment modalities for stage III breast cancer in an inner‐city hospital serving a large AA population. METHODS: A retrospective review was performed for all stage II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 22 publications
0
16
1
Order By: Relevance
“…Although it has been suggested that suboptimal use of adjuvant treatments may explain differences in outcomes, [9,42-46] others have reported little or no differences between black and white patients with regard to chemotherapy administration [73-75]. Differences in adjuvant treatment between black and white women may explain the disparities we noted in stages 2 and 3 [76,77]. However, since the disparities occurred only in the two highest SES categories, we can speculate that patients of all race/ethnicities should have had equal access to adjuvant treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Although it has been suggested that suboptimal use of adjuvant treatments may explain differences in outcomes, [9,42-46] others have reported little or no differences between black and white patients with regard to chemotherapy administration [73-75]. Differences in adjuvant treatment between black and white women may explain the disparities we noted in stages 2 and 3 [76,77]. However, since the disparities occurred only in the two highest SES categories, we can speculate that patients of all race/ethnicities should have had equal access to adjuvant treatment.…”
Section: Discussionmentioning
confidence: 88%
“…Clinical factors that were used to control for chemotherapy outcomes included estrogen receptor (ER) status (positive vs. negative), surgery type (lumpectomy or mastectomy), nodal status (positive or negative), pathological tumor size, and human epidermal growth factor receptor (Her2/neu), which was categorized similar to other reports as positive, negative, or unknown [39]. Comorbidity was measured using the Charlson comorbidity index score [40].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have shown that black women are twice as likely to omit adjuvant treatment, likely to experience delays in the initiation of treatment, and less likely to complete treatment compared with white women (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 97%